Effects of bottom ash and granulated blast furnace slag as fine aggregate on abrasion resistance of concrete - Bilir, Turhan; Yüksel, İsa; Topcu, Ilker Bekir; Gencel, Osman (Walter De Gruyter Gmbh, 2017)
Abrasion resistance is one of the most important durability properties of concrete. Especially, highway, airport and industrial floor pavements should be resistant to abrasion. Recently, many research studies have been carried out on the utilization of industrial by-products in concrete. Granulated blast-furnace slag (GBFS) and bottom ash (BA) are two of these by-products. BA is not generally utilized in concrete and has a limited usage. It is mostly dumped, leading to additional costs and environmental problems. On the other hand, both GBFS and BA have potential for concrete production to provide sustainability. They can substitute fine aggregate thanks to their positive effects on concrete durability. Therefore, the aim of this study was to investigate the abrasion resistance of concretes produced with GBFS and BA substituting fine aggregate. Three different concrete series were produced by replacing fine aggregate with GBFS, BA and both of them by mixing them at equal ratios. The replacement ratios of by-products were 10%, 20%, 30%, 40% and 50% by volume. Compressive strength and Bohme abrasion tests were conducted on series. Results were compared to each other. It can be said that abrasion resistance can be improved by these by-products.
Keywords: abrasion resistance; blast-furnace slag; bottom ash; concrete; durability